Maternal and fetal outcomes of intimate partner violence associated with pregnancy in the Latin American and Caribbean region. Issue 1 (5th October 2013) - Han, Alice; Stewart, Donna E.
Abstract: Background: Very high rates of intimate partner violence during pregnancy (IPV‐P) are reported in Latin America and the Caribbean (LAC) but data on prevalence and obstetric‐related outcomes are limited. Objectives: To conduct a literature review on risk factors, prevalence, and adverse obstetric‐related outcomes of IPV‐P in LAC. Search strategy: Systematic review of studies in MEDLINE (1946–2012) and LILACS (1982–2012), and hand searching of reference lists of included studies. Search terms were variations of partner abuse and pregnancy in LAC. Selection criteria: Studies were excluded if they did not include IPV‐P prevalence or if the perpetrator was not an intimate partner. Data collection and analysis: Study quality was assessed via US Preventive Services Task Force criteria. Main results: In the 31 studies included, prevalence rates ranged from 3% to 44%. IPV‐P was significantly associated with unintended pregnancies and adverse maternal (depression, pregnancy‐related symptom distress, inadequate prenatal care, vaginal bleeding, spontaneous abortion, gestational weight gain, high maternal cortisol, hypertension, pre‐eclampsia, STIs) and infant (prematurity, low birth weight, neonatal complications, stillbirth) outcomes (grade II‐2 and 3 evidence). Conclusions: IPV‐P is highly prevalent in LAC, with poor obstetric‐related outcomes. Clinicians must identify women experiencing IPV‐P and institute appropriate interventions and referrals to avoid its deleterious consequences.